Parental mosaicism in epilepsies due to alleged de novo variants - Møller, Rikke S.; Syrbe, Steffen (Epilepsia, 2019)
Severe early onset epilepsies are often caused by de novo pathogenic variants. Few studies have reported the frequency of somatic mosaicism in parents of children with severe epileptic encephalopathies. Here we aim to investigate the frequency of mosaicism in the parents of children with epilepsy caused by alleged de novo variants. We tested parental genomic DNA derived from different tissues for 75 cases using targeted next-generation sequencing. Five parents (6.6%) showed mosaicism at minor allele frequencies of 0.8%-29% for the pathogenic variant detected in their offspring. Parental mosaicism was observed in the following genes: SCN1A, SCN2A, SCN8A, and STXBP1. One of the identified parents had epilepsy himself. Our results show that de novo events can occur already in parental tissue and in some cases can be detected in peripheral blood. Consequently, parents affected by low-grade mosaicism are faced with an increased recurrence risk for transmitting the pathogenic variant, compared to the overall recurrence risk for a second affected child estimated at approximately 1%. However, testing for parental somatic mosaicism will help identifying those parents who truly are at higher risk and will significantly improve genetic counseling in the respective families.
Gesehen am 15.08.2019